Synthesis, Characterization and Computational Studies of Oxomolybdenum Compounds With Nitrogen Donor Ligands - Kıyak, Harika; Sözüer, Işıl (Izmir Institute of Technology, 2010)
In the first part of the project, the reactions of the solvent-stabilized compound [MoO2Cl2(THF)2] with varios phenylenediamine and some napthalenediamin derivatives in THF at room temperature were investigated. These reactions yielded mononuclear and dinuclear compounds of the type [MoO2Cl2L] and [Mo2O3(.2- O)Cl4(L)2] respectively. In the second part, the reactions of [Mo2O3Cl4(DMF)4] with phenylenediamine and napthalenediamin derivatives were studied under similar conditions and Mo-O-Mo bridged dinuclear oxomolybdenum compounds of the type [Mo2O3(.2-O)Cl4(L)] were obtained. The new compounds were comparatively examined by elemental analysis, FTIR, 1H-NMR and 13C-NMR techniques. In addition, quantum chemical calculations including semi empirical PM3 and DFT methods were carried out to discuss the stability and geometry of the compounds.
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2010
Includes bibliographical references (leaves: 50-57)
Text in English; Abstract: Turkish and English
xii, 153 leaves
Keywords: Molybdenum compounds; Molybdenum--Analysis